2023
DOI: 10.26599/jac.2023.9220740
|View full text |Cite
|
Sign up to set email alerts
|

Greatly enhanced mechanical properties of thermoelectric SnSe through microstructure engineering

Abstract: The outstanding thermoelectric materials SnSe is also known for its inferior mechanical properties, which bring great inconvenience for its application in thermoelectric devices. In this work, SnSe bulks were prepared via a sequential procedure of high-pressure synthesis, ball milling, and spark plasma sintering. The produced polycrystalline samples with a unique microstructure of tightly-bound quasi-equiaxed grains exhibited excellent mechanical properties. The Vickers hardness, compressive strength, and bend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…23,24 Curcumin (Cur), a polyphenolic compound prevalent in turmeric rhizomes, is known for its neuroprotective capabilities, including anti-amyloidogenic effects preventing amyloid protein formation and aggregation, alongside anti-inammatory, antioxidant, and immunomodulatory properties. [25][26][27] Studies have revealed that the dicarbonyl structure of Cur enables it to bind with Fe 2+ and particularly Fe 3+ , positioning Cur as a potential iron chelator, offering promise in inhibiting ferroptosis. 28 The biomedical utility of Cur is constrained by several factors: poor water solubility, a brief half-life, low biological availability, and instability at neutral physiological pH.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Curcumin (Cur), a polyphenolic compound prevalent in turmeric rhizomes, is known for its neuroprotective capabilities, including anti-amyloidogenic effects preventing amyloid protein formation and aggregation, alongside anti-inammatory, antioxidant, and immunomodulatory properties. [25][26][27] Studies have revealed that the dicarbonyl structure of Cur enables it to bind with Fe 2+ and particularly Fe 3+ , positioning Cur as a potential iron chelator, offering promise in inhibiting ferroptosis. 28 The biomedical utility of Cur is constrained by several factors: poor water solubility, a brief half-life, low biological availability, and instability at neutral physiological pH.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SnSe possesses a higher in-plane Young's modulus and shear modulus than the out-of-plane counterparts, as shown in Table S1 (ESI†), which ensures better reliability along the in-plane direction in device fabrication. 40,41…”
Section: Introductionmentioning
confidence: 99%
“…Previously, PbTe was extensively studied as one of the most promising thermoelectric materials at medium temperature, and its low intrinsic lattice thermal conductivity and high carrier mobility guarantee its high thermoelectric efficiency. However, owing to the environmental problems caused by lead, its usage has been gradually prohibited worldwide, and Pb-free thermoelectric materials have recently come under the spotlight. One of the exceptional Pb-free alternatives is SnSe, showing a record-high thermoelectric performance for n- and p-type systems. In addition, other Pb-free thermoelectric materials have also been studied, and AgBiSe 2 , a I–V–VI 2 -group material, has also received attention owing to its low intrinsic thermal conductivity . However, the carrier concentration of pristine AgBiSe 2 is low, and its thermoelectric performance is severely limited by its electrical resistivity.…”
Section: Introductionmentioning
confidence: 99%